Viscoelastic modeling of extrusion damage in elastomer seals. Issue 3 (3rd July 2019) - Windslow, R. J.; Busfield, J. J. C.
ABSTRACT: The viscoelastic behavior of elastomers manifests itself in numerous ways depending on the application. In seals, the viscoelastic response of an elastomer is complex as it depends upon the specific combination of loading pressures, loading rates, chemical environment, temperature and time of loading, and ultimately long-term effects such as creep or stress relaxation can result in seal failure. One specific mechanism encountered in seals under large pressures is extrusion damage. When a seal is pressurized by a fluid, the elastomer is highly constrained; however, there is typically a very small gap between the inner and outer sealing surfaces. Over time viscoelastic creep causes the elastomer to gradually extrude into this gap until the seal ruptures. In this paper the viscoelastic creep behavior of a typical sealing elastomer, NBR, was studied. Compression creep tests were carried out over a range of strains and the measured data were used to develop a strain-dependent viscoelastic material model. The model was then implemented into a finite element analysis (FEA) simulation to study the extrusion creep behavior of an O-Ring seal. Data from the FEA model were then compared against physical test data from equivalent extrusion tests. The FEA model correlated well to the physical test data, with the strain-dependent viscoelastic material model allowing compression creep data to be used to accurately predict extrusion creep.